Candidate genes for anthracnose resistance in Senegalese sorghum: a machine learning-based exploration - Ezekiel Ahn; Insuck Baek; Louis K. Prom; Sunchung Park; Moon S. Kim; Lyndel W. Meinhardt; Clint Magill (Functional & Integrative Genomics, 2026)
Anthracnose, caused by the hemibiotrophic fungal pathogen Colletotrichum sublineola , is a significant constraint to sorghum production worldwide. Developing resistant cultivars is the most sustainable control strategy, but it requires constant additional sources of resistance genes. Here, we applied machine learning (ML) approaches, specifically Bootstrap Forest and Boosted Tree models, to identify single-nucleotide polymorphisms (SNPs) associated with anthracnose resistance in a panel of Senegalese sorghum accessions using publicly available phenotypic data from seedling and 8-leaf stages. The ML models identified five novel high-importance loci distinct from those found by linear model-based Genome-wide association studies (GWAS), while also reinforcing three candidates detected by both methods. The top candidates found through ML algorithms were leucine-rich repeat (LRR), F-box, aspartic peptidase, and jasmonate O-methyltransferase. Several genes were highlighted by both ML and GWAS, strengthening the evidence for their involvement. This study demonstrates the potential of ML to complement traditional GWAS in identifying candidate genes for complex traits, providing a valuable resource for future functional studies and marker-assisted selection efforts to enhance anthracnose resistance in sorghum. Given the constraints of the available population size, these results are best interpreted as an explanatory framework that highlights potential targets for further investigation and guides future functional validation, rather than as a definitive predictive tool.

A haplotype-layered GWAS identifies a multi-trait grain mold resistance hub on sorghum chromosome 5 - Ezekiel Ahn; Sookyung Oh; Louis K. Prom; Seunghyun Lim; Lyndel W. Meinhardt; Clint Magill (Theoretical and Applied Genetics, 2026)

The NPGS Sudanese sorghum core collection encloses novel grain mold resistant germplasm - Hugo E. Cuevas; Louis K. Prom (Genetic Resources and Crop Evolution, 2025)
Grain mold is one of the most devasting diseases in sorghum [ Sorghum bicolor L. (Moench)] that affects the endosperm and deteriorates the pericarp tissue, reducing the quality of the grain. Today, sorghum breeding programs have a limited number of sources of resistance for the development of resistant cultivars. Therefore, the USDA-Agriculture Research Service, National Plant Germplasm System Sudan core collection was assessed to identify new sources of grain mold resistance based on seed emergence and deterioration. A total of 246 accessions were evaluated for two years and a subset of 46 accessions with grain mold resistance were subsequently evaluated for two additional years together with 11 breeding resistant lines from the sorghum association panel. The analysis identified 39 grain mold resistance accessions including seven that showed both high seedling emergence (> 82%) and low seed deterioration (< 2.15). Phylogenetic analysis revealed that five accessions (PI 570382, PI 570776, PI 570330, PI 570702, and PI 570348) that clustered distantly from reference sets and showed both high seedling emergence and low seed deterioration can be classified as new resistance sources. Genome-wide association analysis using 147,069 SNPs identified two genomic regions in chromosome 2 and 3 associated with seedling emergence rate and seed deterioration, respectively. The analysis of both genomic regions found two genes of interest associated with phenylpropanoid metabolic process and phosphorylase kinase. These Sudanese grain mold resistance accessions provide new genetically diverse germplasm for breeding programs and insights in the defense resistance responses.

Genome-wide association study of grain mold resistance in sorghum association panel as affected by inoculation with Alternaria alternata alone and Alternaria alternata, Fusarium thapsinum, and Curvularia lunata combined - Louis K. Prom; Hugo E. Cuevas; Ezekiel Ahn; Thomas Isakeit; William L. Rooney; Clint Magill (European Journal of Plant Pathology, 2020)

GWAS analysis of sorghum association panel lines identifies SNPs associated with disease response to Texas isolates of Colletotrichum sublineola - Louis K. Prom; Ezekiel Ahn; Thomas Isakeit; Clint Magill (Theoretical and Applied Genetics, 2019)

Mating type a locus alleles and genomic polymorphism in Sporisorium reilianum: comparison of sorghum isolates to those from maize - Ghada L. Radwan; Louis K. Prom; Gary Odvody; Clint W. Magill (Australasian Plant Pathology, 2019)

Tapping the US Sweet Sorghum Collection to Identify Biofuel Germplasm - Hugo E. Cuevas; Louis K. Prom; John E. Erpelding (Sugar Tech, 2015)

Evaluation of Gambian and Malian sorghum germplasm against downy mildew pathogen, Peronosclerospora sorghi, in Mexico and the USA - Louis K. Prom; Ramasamy Perumal; Noe Montes-Garcia; Thomas Isakeit; Gary N. Odvody; William L. Rooney; Christopher R. Little; Clint Magill (Journal of General Plant Pathology, 2015)

Assessment of molecular diversity and population structure of the Ethiopian sorghum [Sorghum bicolor (L.) Moench] germplasm collection maintained by the USDA–ARS National Plant Germplasm System using SSR markers - Hugo E. Cuevas; Louis K. Prom (Genetic Resources and Crop Evolution, 2013)